'Slippery turns': Rhetoric and politics in Shakespeare's Coriolanus. (2nd July 2020) - Colclough, David
ABSTRACT: Quentin Skinner argues that a number of Shakespeare's plays depict characters making use of the rhetorical figure paradiastole (the moral redescription of actions), and that in the majority of cases a speaker's use of it is exposed and condemned. The exception is Coriolanus, which uniquely leaves the figure unexposed and the questions it raises unresolved. This article engages with Skinner's argument by suggesting (1) that Coriolanus is perhaps not unique in this respect; (2) that the play's treatment of paradiastole is even more profound than Skinner suggests, and (3) that in Coriolanus paradiastole is presented as the epitome of persuasive speech more generally, which is in turn exposed as inevitably generating an irresolvable pattern of arguments back and forth.